The first sequenced Sphaerotilus natans bacteriophage– characterization and potential to control its filamentous bacterium host. Issue 4 (15th February 2021) - Ferreira, Rute; Amado, Rui; Padrão, Jorge; Ferreira, Vânia; Dias, Nicolina M; Melo, Luís D R; Santos, Sílvio B; Nicolau, Ana
ABSTRACT: Bacteriophages (phages) are ubiquitous entities present in every conceivable habitat as a result of their bacterial parasitism. Their prevalence and impact in the ecology of bacterial communities and their ability to control pathogens make their characterization essential, particularly of new phages, improving knowledge and potential application. The isolation and characterization of a new lytic phage against Sphaerotilus natans strain DSM 6575, named vB_SnaP-R1 (SnaR1), is here described. Besides being the first sequenced genome of a Sphaerotilus natans infecting phage, 99% of its 41507 bp genome lacks homology with any other sequenced phage, revealing its uniqueness and previous lack of knowledge. Moreover, SnaR1 is the first Podoviridae phage described infecting this bacterium. Sphaerotilus natans is an important filamentous bacterium due to its deleterious effect on wastewater treatment plants (WWTP) and thus, phages may play a role as novel biotechnological tools against filamentous overgrowth in WWTP. The lytic spectrum of SnaR1 was restricted to its host strain, infecting only one out of three S. natans strains and infection assays revealed its ability to reduce bacterial loads. Results suggest SnaR1 as the prototype of a new phage genus and demonstrates its potential as a non-chemical alternative to reduce S. natans DSM 6575 cells. Abstract : A new bacteriophage infecting S. natans DSM 6575 is here isolated, and this new phage, SnaR1 was characterized and its potential as a non-chemical to control S. natans DSM 6575 strain was assessed.